Evaluation of Harvesting and Marketing Activities with GIS in Beech Log Production Areas (İnebolu Forest Sub-District Sample) - Buğday, Ender; Erkan Buğday, Seda (Eurasian Journal of Forest Science, 2019)
In this study focuses on the planning of harvesting-production and marketing process in beech stands. İnebolu Forest Management District (FMD) has been designated as the study area. Potential beech timber forest with high economic values were identified, and estimated log production quantities were determined. In the marketing phase of the products obtained from harvesting, the best-optimum marketing place points for Forest Sub-district Directorates were determined with the help of geographic information systems. In this study, as the potential for beech timber areas of the Inebolu FMD, a total of 1482.2 hectares of land could be operated with timber production-harvesting oriented. According to the results, 82% of the pure and mixed beech forests could be directed to the stumpage and ramp sale and 18% to depot sales. In this respect, during the production-harvesting and after production, the periods of encountering abiotic and biotic pests of beech logs are reduced. So degradation and economical losses could be minimized.
Keywords: Forest harvesting; marketing; forest product; GIS; 15. Life on land